Incidence of left atrial appendage thrombus on pre-procedural TOE before catheter ablation of atrial tachyarrhythmias. (14th October 2021) - Wegner, F; Radke, R; Ellermann, C; Wolfes, J; Fischer, A.J; Baumgartner, H; Eckardt, L; Diller, G.P; Orwat, S
Abstract: Introduction: Transoesophageal echocardiography (TOE) is routinely performed before catheter ablation of atrial tachyarrhythmias to rule out the presence of possible left atrial thrombi. However, data to support this practice are scarce. Methods: We analysed consecutive pre-procedural TOE in a high-volume electrophysiology centre for the presence of left atrial thrombi and a relevant flow reduction in the left atrial appendage (LAA) defined as LAA sludge or pronounced spontaneous echo contrast. Possible predictors of reduced flow were recorded and compared in a multivariate logistic regression analysis. Results: 1676 consecutive TOE were included (1122 before pulmonary vein isolation (PVI), 436 before atrial flutter ablation, 166 before other EP studies in patients with a history of atrial tachyarrhythmias). 543 patients (32%) were female, mean age was 63±12 years and BMI was 27±5 kg/m 2 . Nine patients (0.5%) had an LAA thrombus on pre-procedural TOE. Ninety-five further patients (5.7%) had a relevant reduction in LAA flow as characterized by LAA sludge or spontaneous echo contrast. Further patient characteristics by LAA flow state are shown in the table. While a higher CHA2DS2-VaSc-Score was associated with the presence of LAA sludge and LAA thrombus (p=0.01), no further clinical parameters such as choice of oral anticoagulation agent were independently predictive of reduced flow velocities or thrombus in a logistic regression model (see table). Importantly, LAA thrombi also occurred in patients with a CHA2DS2-VaSc-Score ≤1 (n=1) or in sinus rhythm (n=2). Of note, 6 out of 9 patients with a LAA thrombus were anticoagulated with phenprocoumon. Conclusion: LAA thrombus is a rare occurrence before an elective catheter ablation. In patients with CHA2DS2-VaSc-Score ≤1 the likelihood of LAA thrombus is so low (0.2%) that it may be considered to give up routine TOE before an EP study/ablation. Funding Acknowledgement: Type of funding sources: None.